2014
DOI: 10.1074/jbc.m114.597955
|View full text |Cite
|
Sign up to set email alerts
|

Structural Asymmetry of the Terminal Catalytic Complex in Selenocysteine Synthesis

Abstract: Background: SepSecS catalyzes the terminal step of selenocysteine synthesis in a reaction that requires tRNA Sec . Results: SepSecS simultaneously binds up to two tRNAs in a cross-dimer fashion. Conclusion:The SepSecS-tRNA Sec complex is asymmetric: one dimer is a noncatalytic platform that binds tRNAs, whereas the other one catalyzes the reaction. Significance: The study proposes allosteric regulation of selenocysteine and selenoprotein synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 48 publications
5
14
0
2
Order By: Relevance
“…Until detailed studies are performed that establish the in vivo ratios of all of the factors, it will not be possible to sort out whether eEF1A must be actively prevented from Sec-tRNA Sec binding or whether there simply is never an opportunity for binding due to the stoichiometry of factors. Along those lines, a recent study shows that the endogenous SepSecS enzyme that converts Ser to Sec after serine phosphorylation is present as a more than 3-fold molar excess over total tRNA Sec in human hepatoma cells, thus supporting the idea that Sec-tRNA Sec may be “channeled” onto eEFSec by virtue of its complex synthetic pathway (French et al, 2014). …”
Section: 2 Elongation Factor Specificitymentioning
confidence: 82%
“…Until detailed studies are performed that establish the in vivo ratios of all of the factors, it will not be possible to sort out whether eEF1A must be actively prevented from Sec-tRNA Sec binding or whether there simply is never an opportunity for binding due to the stoichiometry of factors. Along those lines, a recent study shows that the endogenous SepSecS enzyme that converts Ser to Sec after serine phosphorylation is present as a more than 3-fold molar excess over total tRNA Sec in human hepatoma cells, thus supporting the idea that Sec-tRNA Sec may be “channeled” onto eEFSec by virtue of its complex synthetic pathway (French et al, 2014). …”
Section: 2 Elongation Factor Specificitymentioning
confidence: 82%
“…Recently, French et al . have shown that the SepSecS tetramer is able to bind to one or two tRNA Sec molecules ( 45 ), but the binding preference of hSerRS to tRNA Sec is not clear. In this study, we obtained two types of complexes of crystals in different stoichiometry to rule out the possibility of crystallization artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…In order to examine whether the solution conformation and interactions of SepSecS with tRNA Sec parallel those observed in the high-resolution structure, French and co-workers [54] performed a series of sedimentation velocity, SEC-MALLS (size exclusion chromatography coupled with multiangle laser light scattering) and SAXS (small angle X-ray scattering)…”
Section: The Terminal Catalytic Complex In Selenocysteine Synthesismentioning
confidence: 99%